Alpha-Lipoic Acid Protects Co-Exposure to Lead and Zinc Oxide Nanoparticles Induced Neuro, Immuno and Male Reproductive Toxicity in Rats - Deore, Monika S.; S, Keerthana; Naqvi, Saba; Kumar, Anoop; Flora, S. J. S. (Frontiers in Pharmacology, 2021)
We evaluated the neuro-, immuno-, and male reproductive toxicity of zinc oxide nanoparticles (ZnO NPs) alone and in combination with lead acetate. We also studied the therapeutic role of α-lipoic acid postexposure. Lead (10 mg/kg, body weight), ZnO NPs (100 mg/kg, bwt) alone, and their combination were administered orally in Wistar rats for 28 days, followed by the administration of α-lipoic acid (15 mg/kg, bwt) for the next 15 days. Our results demonstrated protective effects of α-lipoic acid on lead and ZnO NP–induced biochemical alterations in neurological, immunological, and male reproductive organs in rats. The altered levels of blood δ-aminolevulinic acid dehydratase (ALAD), immunoglobulins (IgA, IgG, IgM, and IgE), interleukins (IL-1β, IL-4, and IL-6), caspase-3, and tumor necrosis factor (TNF-α) were attenuated by lipoic acid treatment. Lead and ZnO NP–induced oxidative stress was decreased by lipoic acid treatment, while a moderate recovery in the normal histoarchitecture of the brain section (cortex and hippocampus) and testes further confirmed the neuro- and male reproductive toxicity of lead and ZnO NPs. We also observed a significant decrease in the blood metal content in the animals treated with lipoic acid compared to the lead-administered group, indicating the moderate chelating property of lipoic acid. It may thus be concluded that lipoic acid might be a promising protective agent against lead and ZnO NP–induced alterations in the neurological, immunological, and reproductive parameters.